The Problems And Concepts of The Land Management Rights Improvement in Batam City - Ampuan Situmeang; Winsherly Tan; Elza Syarief; Abdul Rachman (Universitas Islam Negeri Antasari Banjarmasin, 2021)
The purpose of this study is first, to know about the basic concept of land management rights in Batam City in terms of improving people's welfare. Second, knowing about improving the quality of land management rights in Batam City.The method used by this study is an empirical legal research. The type of data used is primary data, namely those obtained from interviews with the public community, government officers of Batam City, BP Batam and the District office and also Sub-district office. As well as conducting observations in the old village of Tanjung Uma and the old village of Nongsa. Both also use secondary data consisting of primary legal materials, namely the 1945 Constitution and Law Number 5 of 1960 concerning Agrarian Principles.Based on the results of the study, first, it was found that the Implementation of Land Management Rights in Batam became problematic after Indonesia entered the Reform phase with the enactment of Law No. 22 of 1999 on Local Government or Regional Autonomy Law, Law No. 53 of 1999 on The Establishment of Batam city and the Batam Mayor Decree No. 105 of 2004 on The Establishment of 37 Old Village Points. Second, through the socio-legal research, the researcher suggests that the Central Government and the Regional Government of the Riau Islands Province as well as the Batam City Government and BP Batam to immediately restructure the land policy regulations in Batam and synchronize land policies so that Batam people can obtain certainty of land rights as guarantees for their welfare in the future. .